The Influence of Personality, Shop Enjoyment, and Impulsive Buying Tendency on Impulsive Buying Behavior in Transmart Ngagel Surabaya - Dian Savitri; Nurul Aini; Joko Suyono (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: This study aims to analyse the correlation between personality, shop enjoyment, impulsive buying tendency and impulsive buying behaviour statistically. Design/methodology/approach: This study is a quantitative study. Findings: From all the hypotheses proposed, only 3 out of 7 that are significant and supported Research limitations/implications: The respondents of the study are 100 consumers of Transmart Ngagel, Surabaya. Practical implications: 3 out of 7 hypotheses are supported and significant. Paper type: This is categorised as case study. Keyword: impulsive buying behaviour, impulsive buying tendency, personality, shop enjoyment